5 - Pour le «Développement» du Tiers-Monde: Critique d'une Notion Univoque dans l'Histoire Universelle des Civilisations * - DIALLO, Ibrahima (Africa Development, 1984)
* Article déjà publié dans « Connaissance et Vie - Revue des Mondes en Emergence» Vol.2, No. 4 - Nov/Déc. 1982, Sherbrooke, Québec (Canada). The concept of development does not belong to the continuum of the universal history of civilizations. It is related to the specific history of Western civilization. In spite of the variety in the philosophical and religious, ancient and esthetical, scientific and technical contributions made by ancient civilizations, the latter helped one another come to fruition. On the contrdry, the outstanding feature in the Western industrial civilization is its expansionist and dominating character which negates and destroys other civilizations' values so as to promote the expansion of its own dominant scientific and technical values which are yet dependent on ancient cultures. The ethics and the existential philosophy on which the Western development model is based is the first point of departure between these civilizations. These ethics and philosophy are rooted in the ancient greek commercial civilization which guides man toward a new ambition, a new destiny, through its Promethean individualism. Thus, the Western industrial civilization which is in open contra- diction with the history of its own emergence, sanctions a linear view of the development of society which is based on the continuous development of science and technology. This civilization constitutes the apex of the scientific and technical development and therefore the present model. Development becomes therefore an ideology whose alienating belief is rooted in a material growth and in an adequate progress, whatever the area. It suggests the industrial civilization model as an objective to be reached by every human society. The two liberal and marxist ideologies into which the world is divided fit into this view, as both sanction the concept of an unlimited in- crease of material productive forces and of consumption goods and as both lay more emphasis on scientific thoughts and technical know-how than on other non-experimental forms of thoughts and actions. Yet, there are several past and present examples which are dispara- ging to this univoca!, global view of development: the disappointment, in the light of changing Third World economies, which followed an optimism generated by the first attempts at theorizing the various stages of growth. the crisis in the economic growth of industrialized countries. the failure in negotiations for the establishment of a new international economic order... There still is a basic paradox between objectives and means in the universal civilization model which is based on the suggested economic system. Due to this paradox, the excessive, increasingly sophisticated needs of a few - that is a minority - call for the non-satisfaction of the basic material needs of a majority. From the perspective offered by the modern consumer society, it appears that progress rests on an inequality principle which is, in fact, a pre- requisite for it. Today we have to break new grounds by selecting options which will reconcile man with the best of the past civilizations legacy. African civilizations which are about to lose their souls today, abound with enough examples of generosity and wisdom in the past, to maintain a sense of equality ( rather than inequality) and of harmony between individual and collective interests in grassroot communities. Both industrialized Western countries and under-developed Third- World countries will have to become aware of these points in order to shape a common future.